Growth performance of tilapia (Oreochromis sp.) with different doses of pellets in floating net cages (KJA) - Putri, Hylda Khairah; Susilawati, Susilawati; Setiawan, Agus; Sarmila,; Mudlofar, Farid; Warastuti, Sri (JURNAL MINA SAINS, 2024)
Feed is an essential input in aquaculture activities. Feed affects the growth and survival of fish, which can increase the benefits of aquaculture activities. However, the leftover feed can accumulate organic matter from the digestive process and metabolic waste such as feces and inorganic materials such as ammonia, nitrite, and nitrate in the waters. The more feed used, the more organic and inorganic waste accumulates in the aquaculture media. This study aims to analyze the effect of commercial pellet doses on the growth performance of red tilapia (Oreochromis sp.) maintained in the floating net cage (KJA) system in the Mempawah River, West Kalimantan. The study was conducted experimentally using a completely randomized design (CRD) method with four different feed dose treatments and three replications. Treatment 1 was the provision of a commercial pellet dose of 2%; Treatment 2 was the provision of a commercial pellet dose of 3%; Treatment 3 was the provision of a commercial pellet dose of 4%, and Treatment 4 was the provision of a commercial pellet dose of 5%. Tilapia seeds were maintained with the treatment for 40 days. The results showed that administering a 5% commercial pellet dose gave the best absolute, relative, and daily growth compared to other treatments. The survival rate for tilapia seeds maintained in the floating net cage system was best in treating 3% and 4% feed doses.